Out-of-sequence thrusting in Himalaya: Modification of wedge extrusion and channel flow models - Dubey, CS; Sharma, BK; Catlos, EJ; Marston, RA (Himalayan Journal of Sciences, 2008)
Himalayan Journal of Sciences Vol.2(4) Special Issue 2004 pp. 130